Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s42506-022-00118-0
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of respiratory tract infections in children under 5 years of age in a low–middle-income country

Abstract: Background Respiratory tract infections (RTIs) are among the most commonly encountered major public health problems, with a higher prevalence of lower RTIs among children and more generally the poor. The present study aimed to describe the pattern of respiratory tract infections in Egyptian children aged under 5 years and explore possible associations between socio-demographics and nutritional status and types of RTIs. Methods Over 6 months beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
(22 reference statements)
0
0
0
2
Order By: Relevance
“…17,18 In a study by El-Koofy et al conducted in Egypt, the authors did not find in-house overcrowding as a risk factor of ARIs, also the study also did not reported significance association of residential area with ARIs. 2 In this study we found that being rick considerably reduces the probability of ARI hospitalisation. However, it is believed that having too many people living in one place is a sign of social marginalisation and poverty.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…17,18 In a study by El-Koofy et al conducted in Egypt, the authors did not find in-house overcrowding as a risk factor of ARIs, also the study also did not reported significance association of residential area with ARIs. 2 In this study we found that being rick considerably reduces the probability of ARI hospitalisation. However, it is believed that having too many people living in one place is a sign of social marginalisation and poverty.…”
Section: Discussionmentioning
confidence: 57%
“…1 Children and individuals of lower socioeconomic status are particularly susceptible to a higher occurrence of lower RTIs. 2 Severe acute respiratory tract infections (RTIs), specifically pneumonia in children under the age of five, result in hospitalisations and mortality in approximately 15% of instances. 3 According to the findings of the Global Burden of Disease research conducted in 2019, lower respiratory tract infections have been identified as the second leading source of burden among children.…”
Section: Introductionmentioning
confidence: 99%
“…The demographic profile of our study, dominated by a young median age of three years and a male predominance, is consistent with global pediatric cohorts diagnosed with ARIs. This demographic may be vital in interpreting antibiotic usage patterns since younger children, particularly males, are often more susceptible to respiratory infections due to their developing immune systems and narrower airways [ 19 - 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Шляхом лінійного регресійного аналізу із Voloshin O.M, Marushko Yu.V., Savchenko I.I. Найчастіше в наукових публікаціях повідомляється, що суттєві й різноспрямовані -у бік зменшення або збільшення -відхилення фізичного розвитку дітей зумовлюють їхню вищу схильність до РРІ [8,10,14,15,28]. З іншого боку, відзначається наявність вираженого негативного впливу частих епізодів ГРІ на їхні антропометричні показники [11,18,19,29].…”
Section: матеріали та методиunclassified
“…Повідомляється, що недостатність харчування є одним із важливих предикторів, що зумовлює вищий рівень захворюваності на ГРІ з ураженням нижніх дихальних шляхів у дітей до 2 років [8]. Затримка росту й виражене схуднення є достатньо розповсюдженими проявами в дітей віком до 5 років, госпіталізованих із приводу ГРІ [9].…”
unclassified